Agriculture : uncertain times. - HORNER, Simon (1997)
Examines the importance of agriculture to the local economy. Notes that all three of Grenada's significant products - nutmeg, cocoa and bananas - have faced problems in recent years. Points out that despite the obvious potential, uncertain times lie ahead for the agriculture sector in Grenada.